Day 4 good morula embryo transfer provided compatible live birth rate with day 5 blastocyst embryo in fresh IVF/ET cycles - Ryh-Sheng Li; Yuh-Ming Hwu; Robert Kuo-Kuang Lee; Sheng-Hsiang Li; Ming-Huei Lin (Elsevier, 2018)
Objective: Embryo transfers during cleavage stage (day 2 or day 3) and blastocyst stages (day 5 or day 6) are common in current daily practice in fresh IVF/ET cycles. Data regarding transferring day 4 embryos, morula/compact stage, is still restricted and the grading system is also inconsistent, as between IVF clinics. This study provided a new detailed classification system for morula/compact stage embryos and compared successes rates between day 4 and day 5 ET. Materials and methods: This was a retrospective study. A review of medical records from January 1st, 2013, to December 31st 2015, performed for all conventional insemination and ICSI cycles with a GnRH-antagonist protocol at the Infertility Division of MacKay Memorial Hospital in Taipei City, Taiwan. Results: There were 427 cycles included in our study, 107 in study group (day 4 MET) and 320 in control group (day 5 BET). Pregnancy rates and live birth rate were compatible, as between morula embryo transfer (MET) and blastocyst embryo transfer (BET). The implantation rate (36.3% vs. 39.6%, respectively, p = 0.500), clinical pregnancy rate (49.5% vs. 51.9%, respectively, p = 0.737), and live birth rate (42.1% vs. 45.6%, respectively, p = 0.574) were statistically insignificant between groups. The term birth rate was statistically higher in the MET group than in the BET group (95.7% vs. 79.5%, respectively, p = 0.006). When the clinical outcomes between day 4 good MET and day 5 good BET were compared, the results were compatible. The implantation rate (48.8% vs. 41.1%, respectively, p = 0.335), clinical pregnancy rate (55.0% vs. 53.2%, respectively, p = 0.867), and live birth rate (47.5% vs. 47.1%, respectively, p = 1.000) showed no significant difference. The term birth rate was also higher in day 4 good MET group than in day 5 good BET group (100% vs. 78.3%, respectively, p = 0.025). Conclusion: In this study, we performed day 4 MET avoid BET on Sunday. The grading system we provided was more detailed for embryo selection and it was easier to remember. Our data showed that morula embryo transfer might be a flexible, easier and applicable method for embryo transfer in daily routine.